2020
DOI: 10.1136/bmjdrc-2020-001372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on circulating and urinary mitochondrial DNA copy numbers in obesity with or without diabetes

Abstract: IntroductionRecent studies have suggested that extracellular circulating and urinary mitochondrial DNA (mtDNA) are associated with mitochondrial dysfunction in obesity and type 2 diabetes mellitus (T2DM). However, the changes to cell-free serum and urinary mtDNA after bariatric surgery in patients with obesity with T2DM have not been investigated to date.Research design and methodsWe prospectively recruited patients with obesity (n=18), and with obesity and T2DM (n=14) who underwent bariatric surgery, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…Indeed, by measuring the urinary MtDNA content in patients with residual urine, we found that although not statistically significant, there was a negative correlative trend between urine MtDNA and ccf‐MtDNA. The results of this study strongly support the idea that kidney is responsible for scavenging plasma MtDNA 25,33 . Previous studies proposed that circulating MtDNA is originated by passive leakage from broken mitochondria 7 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, by measuring the urinary MtDNA content in patients with residual urine, we found that although not statistically significant, there was a negative correlative trend between urine MtDNA and ccf‐MtDNA. The results of this study strongly support the idea that kidney is responsible for scavenging plasma MtDNA 25,33 . Previous studies proposed that circulating MtDNA is originated by passive leakage from broken mitochondria 7 .…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study strongly support the idea that kidney is responsible for scavenging plasma MtDNA. 25,33 Previous studies proposed that circulating MtDNA is originated by passive leakage from broken mi-…”
Section: Ta B L E 4 Logistic Regression Analysis Results Of the Assoc...mentioning
confidence: 99%
“…This is in line with the observation that ecDNA correlates with body fat and inflammation but not with BMI (55). Similarly, bariatric surgery as the most effective treatment of obesity leads to a decrease of ecDNA but only in diabetic subjects (56).…”
Section: Discussionsupporting
confidence: 87%
“…For this reason, mtDNA methylation appears as a promising mediator between environmental exposure (i.e., diet) or metabolic conditions (i.e., obesity) and mitochondrial health. In addition, the blood level of mtDNA copy number (mtDNAcn) has emerged as a promising biomarker, especially in obesity [ 32 , 33 ], metabolic diseases (e.g., type 2 diabetes) [ 34 36 ], and CVD [ 37 , 38 ], and clinical interventions have been shown to modulate this parameter [ 39 ]. Despite the link between mtDNA, environmental exposures and complex diseases, and mtDNA's potential role as a biomarker, no previous research projects investigated mtDNAcn in people with increased body weight correlating it with the nutritional status, the abundance of 1CC intermediates, and with mtDNA methylation.…”
Section: Introductionmentioning
confidence: 99%